2018
DOI: 10.1002/csr.1479
|View full text |Cite
|
Sign up to set email alerts
|

When Advertising Highlights the Binomial Identity Values of Luxury and CSR Principles: The Examples of Louis Vuitton and Hermès

Abstract: In a controversial context, luxury houses have followed the ancestral values of artisanal production, with respect for materials, the environment, and people, thereby facilitating their current application of the principles promoted by Corporate Social Responsibility (CSR). They used to publish their CSR results in their annual reports and via their websites but can also do it implicitly through their advertisements. For the first time, the advertising creation and decoding process together with a semiotic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 62 publications
1
9
0
1
Order By: Relevance
“…Scholarly research has begun documenting sustainability efforts of luxury brands (Athwal et al 2019 ; Anido Freire and Loussaïef 2018 ; Han et al 2017 ; Macchion et al 2018 ; Mititelu et al 2014 ), suggesting that incorporation of sustainability into luxury brands should not be ignored (Winston 2016 ). However, since the first mention of sustainable luxury as a separate construct by Bendell and Kleanthous’s ( 2007 ), there has been an ongoing debate on whether the concept of luxury is even compatible with sustainability (Kapferer and Michaut-Denizeau 2014 ; Achabou and Dekhili 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholarly research has begun documenting sustainability efforts of luxury brands (Athwal et al 2019 ; Anido Freire and Loussaïef 2018 ; Han et al 2017 ; Macchion et al 2018 ; Mititelu et al 2014 ), suggesting that incorporation of sustainability into luxury brands should not be ignored (Winston 2016 ). However, since the first mention of sustainable luxury as a separate construct by Bendell and Kleanthous’s ( 2007 ), there has been an ongoing debate on whether the concept of luxury is even compatible with sustainability (Kapferer and Michaut-Denizeau 2014 ; Achabou and Dekhili 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Luxury brands are increasingly criticized for their unethical and unsustainable practices. This has led to some brands committing more to sustainable and socially responsible initiatives (Anido Freire and Loussaïef 2018 ; Mititelu et al 2014 ). While there is increasing scholarly attention given to sustainable luxury research, a recent systematic review of literature between 2007 and 2018 revealed that few studies have sought to understand sustainability within the luxury marketplace (Athwal et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quality is furthermore associated with a high level of safety and with the comfortability and usability of the luxury product (Heine & Phan, ). The durability of the luxury product is also part of the quality aspect (Anido Freire, ; Anido Freire & Loussaïef, ; Heine & Phan, ), and part of the durability of luxury products is that they are timeless and unique (Carcano, ). Furthermore, the level of service, both when purchasing the product and in after‐sales interactions, is part of the quality experience of a luxury product (Heine & Phan, ).…”
Section: The Conceptual Framework: Can Luxury Products Be Circular?mentioning
confidence: 99%
“…Both Kapferer () and Keller () suggest that this does not only apply to the luxury product itself but also to the services surrounding it, such as extended warranties and service schemes. Luxury products are also often associated with timeless design (Anido Freire & Loussaïef, ; Carcano, ; Hennigs, Klarmann, & Labenz, ; Joy, Sherry, Venkatesh, Wang, & Chan, ; Kapferer & Bastien, ) and, therefore, are less likely to be perceived as obsolete or out of fashion. This further increases the likelihood of a long service life of the product, of reuse, and of maintenance of the product.…”
Section: The Conceptual Framework: Can Luxury Products Be Circular?mentioning
confidence: 99%
“…Transparency also requires that companies disclose, inform, and publish their CSR behaviours. In this regard, some global companies have sought to highlight their CSR achievements by including such information in their advertising, which has favoured the improvement of its brand image (Anido Freire & Loussaïef, 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 99%